Efektivitas Program Generasi Berencana Dalam Pengembangan Keluarga Berkuallitas Di Kecamatan Dungingi Kota Gorontalo - Ikbal Naim; Rusli Isa; Rustam Tohopi (Gorontalo State University, 2022)
ABSTRACT The purpose of the research is to find out how effective the policies and constraints in implementing the Generation Planned (GenRe) program are in Dungingi District, Gorontalo City, with indicators of organizational characteristics, technological characteristics, environmental characteristics, and worker characteristics. This research method uses qualitative descriptions using data sources conducted through in-depth interviews with informants. The findings of the research show that of course the implementation of the GENRE program will be more effective when the participants are active, but from the data obtained by researchers in the field, members of the PIK-R and BKR groups have not been maximal in carrying out their duties as evidence in the field that many socialization programs are not carried out properly, thisis based on the lack of motivation for workers who run the GENRE program and human resources. Factors that determine the effectiveness of policies and obstacles to implementing the Generation Planning (GenRe) program in Dungingi District, Gorontalo City. which includes organizational characteristics, technology, environment are implemented well, but still need to consider the characteristics of workers in the implementation of the GENRE program in Dungingi District, Gorontalo City.